Does Basel II affect the market valuation of discretionary loan loss provisions? - Hamadi, Malika; Heinen, Andréas; Linder, Stefan; Porumb, Vlad-Andrei (Journal of Banking & Finance, 2016)
We use a sample of banks from 24 European countries to investigate whether the adoption of the Basel II Capital Accord in 2008 affects the market valuation of discretionary loan loss provisions (DLLPs). Although Basel II lowers the incentives of internal ratings-based (IRB) banks to recognize income-increasing DLLPs in an opportunistic manner, it has no such impact on the remaining banks, which adopt the Standardized methodology. We use this setup in a difference-in-difference (DiD) design, where Standardized banks act as a control group. Our evidence supports the three hypotheses that, for IRB relative to Standardized banks, Basel II is associated with (i) less income-increasing DLLPs and (ii) less income-smoothing via DLLPs, which enhances the informational content of DLLPs about future loan losses and leads to (iii) higher market valuation of DLLPs. Our findings are timely and have policy implications for future regulatory developments in the banking industry.